Characteristics and outcomes of pharmacy-supported transitions of care interventions in emergency departments: a scoping review - Eman Alhmoud (13955766) (2025)
Introduction Transitions of care (ToC) services are essential for maintaining care continuity. The complex and fast-paced nature of care and high patient turnover in emergency departments (EDs) create unique challenges and opportunities for improving transitional care. Although the benefits of pharmacy-supported ToC interventions are established in non-ED settings, there is a lack of evidence exploring their characteristics and outcomes in EDs. Aim We aimed to identify and present the available evidence regarding the characteristics and outcomes of pharmacy-supported ToC interventions beyond medication reconciliation, as the sole intervention, in EDs. Method This review was conducted in accordance with the Joanna Briggs Institute methodology and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews guidelines. A literature search was performed across PubMed, Embase, CINAHL, Web of Science, and grey literature from their inception until 22/12/24. The search included terms related to pharmacy, transitional care, and EDs. Data was extracted using a custom tool adapted from the Template for Intervention Description and Replication checklist, which was used to assess the articles’ compliance with the items. Results A total of 64 publications were included. Most studies (n = 58) enrolled adult patients, with 13 focusing on older adults. Most interventions were delivered by pharmacists in collaboration with other healthcare providers in 64% of studies. Interventions were most implemented post-discharge (54.7%), followed by arrival to the ED (42.2%). Around 90.6% of interventions included two or more activities, combining medication reconciliation, discharge planning, and follow-up care. Most studies focused on health utilization metrics (e.g., readmission rates) as their outcomes (28.8%). Positive effects were observed on medication safety, antibiotic stewardship, patient satisfaction, and resource use. However, pediatric populations and intrahospital transitions were underrepresented. Conclusion This scoping review highlights the potential of pharmacist-supported transitional care interventions within EDs. The role of pharmacists in ToC interventions in emergency settings is evidently growing. Despite this, critical gaps persist in reporting and implementing these interventions. Future research is needed to systematically explore such initiatives and evaluate their implementation and long-term impact. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-025-02057-0